HUBUNGAN DEVELOPING OTHERS DENGAN KINERJA BIDAN DALAM PEMBERIAN TABLET FE PADA IBU HAMIL DI PUSKESMAS KOTA SURABAYA - Agus Aan Adriansyah (Universitas Jember, 2015)
Social skills closely related to the performance results obtained. Developing others, is an indicator of social skills. Developing others is an effort to understand the needs of others to flourish and help them to improve. A midwife is expected to have the ability developing others in fulfilling its performance in providing services to pregnant women, particularly in programs providing Fe tablet. This study was conducted by using cross sectional approach. The population in this study is the center midwife who numbered 281, spread over 62 centers of primary health care in the city of Surabaya. While the sample in this study was 65 midwives. The data collection is done with reference to field research by direct interview using a questionnaire method, and the method of observation. The data analysis was conducted on the univariable descriptive analysis with cross bivariable cross tabulation, and analysis techniques Ordinal Logistic Regression. Most of the midwives at the health center of Surabaya has competence developing others in the levels were very good and had a good performance in the activity of granting Fe tablets to pregnant women at health centers. Among developing others with the performance of midwives have a close relationship. The better the developing others owned midwife, the better the performance of the resulting outcomes. Keyword: Developing others, Midwives Performance, Fe Tablet, Pregnant Mother